Pengaruh Penambahan Berbagai Bahan Makanan terhadap Daya Terima dan Kadar Protein Cookies Sebagai PMT untuk Balita Stunting: The Effect of Addition of Various Food Ingredients on Acceptance and Protein Content of Cookies as PMT for Stunting Toddlers - Rumida Rumida; Tiar Lince Bakara; Mincu Manalu; Ginta Siahaan (Amerta Nutrition, 2023)
Background: Stunting is a developmental failure that occurs due to poor nutrition in the past, and almost 25% of children under five worldwide experience it. The World Health Organization determined that stunting in the world was <20% in 2018, while it was 30.8% in Indonesia. Cookies are meals liked by people of all ages and can be given to eradicate stunting. They can be processed from various food ingredients that have rich protein content. Objectives: This study aimed to determine  cookie acceptance for protein content for stunted children Methods: The experimental research used a completely randomized design (CRD) for five treatments: formulations A, B, C, D, and E, with three repetitions. The acceptance test was also carried out on 15 stunted toddlers using the Comstock test (food scraps). The selected cookie formulations were tested for protein content using the Kjehdal method. Data analysis was continued using the variance analysis (ANOVA) test, followed by the Duncan method. Results: The results of the ANOVA test showed that cookies significantly influenced the level of aromatic aspect (p=0.011) and contained 12.91 grams of protein. Duncan's test showed significant differences in cookies' taste and aroma (treatments C and A). Conclusions: Treatment A, which has certain cookies' formulation and sensory characteristics, i.e., color, texture, taste, and aroma, contains higher protein and contributes to the adequacy of nutrition in children aged 3-5 years by 57.37%.